CALCULATION OF THE RATING OF ECOLOGICAL DEVELOPMENT OF INDIVIDUAL REGIONS OF THE REPUBLIC FOR 2021 - Tsublianok, Darya V.; Vadeika, Marharyta V.; Hramadskaya, Alena I. (Journal of the Belarusian State University. Ecology, 2023)
The rating of ecological development of the regions of the Republic of Belarus is designed to reflect the activities in the field of rational nature management and environmental protection of state bodies whose competence includes environmental protection issues, executive authorities, public associations, citizens in the relevant territories with the possibility of comparing information in an administrative-territorial context.